RAINWATER HARVESTING SYSTEM DESIGN AND UTILIZATION FOR CIBE BUILDING - SALSABILLA (NIM: 15313093), ANISA
Along with the development of the era, people realize that water demand is increasing and the availability is increasingly limited. The average rainfall in Indonesia is quite high which is 2000-3000 mm/year or 150-300 mm/month. Until now the rainwater management system in CIBE Building still adopt the old paradigm which is to drain rain water as fast as possible to the nearest drainage. This is unfortunate given that rainwater can be utilized on the surface by keeping them in reservoirs, catchment areas, or even used as a source of clean water and drinking water. Therefore, in this project it is necessary to know the volume of rainwater that can be harvested using hydrological analysis and the amount of water demand in CIBE Building to determine rainfall utilization. Based on the results of laboratory tests and secondary data of rainwater quality in Bandung, parameters that do not meet the quality standard are pH (4.86), cadmium (5.62 μg/L), lead (76.68 μg/L),and selenium (21.89 μg/L).Therefore, the processing unit used is acid neutralizer, rapid sand filtration for clean water utilization, reverse osmosis for potable utilization, and desinfection. The components designed in this rainwater harvesting system consist of gutters, downspout, first-flush diverter, storage tanks, and treatment units.